Analisis Metode Certainty Factor dalam Akomodasi Inexact Reasoning pada Sistem Pakar Diagnosa Penyakita Jantung - desiani, anita; Lubis, Andika Cristian; Irmeilyana (Journal of Information Technology, 2023)
Heart is an important organ in the body that is useful as a blood pump with the aim of meeting the needs of oxygen and nutrients to the body. If the heart has impaired performance, blood flow in the body becomes abnormal and can lead to heart disease. The types of heart disease that commonly increase the death rate are coronary heart disease, heart valve disease, and heartbeat disorders (arrhythmia). In this case, there is a need for early detection in a complex manner through a high-accuracy system, namely an expert system. Expert systems contain detailed information about the disease being diagnosed. The Certainty Factor method is a certainty factor method that can overcome the uncertainty (inexact reasoning) of experts in making decisions based on disease symptoms and an interval scale of confidence in the symptoms given by system users. The application of the expert system begins with assembling a system involving the acquisition of knowledge sources explored from heart specialist experts. The analysis obtained on accommodating inexact reasoning on symptoms and the interval scale of the system user's confidence level for 5 test data based on the symptoms felt by the disease sufferer resulted in prediction accuracy for each type of heart disease where 90.46% coronary heart disease in the first test data, 80.76% arrhytmia in the second test data, 87.43% heart valve disease in the third test data, 93.12% coronary heart disease in the fourth test data, and 93.96% heart valve disease in the fifth test data. The application of the certainty factor method to the expert system produces appropriate prediction accuracy so that the expert system designed is effective for measuring certainty in diagnosis and it can be an alternative to early detection of several types of heart disease.